2020
DOI: 10.3389/fimmu.2020.01333
|View full text |Cite
|
Sign up to set email alerts
|

Development of Spherical Nucleic Acids for Prostate Cancer Immunotherapy

Abstract: Although the strategy of therapeutic vaccination for the treatment of prostate cancer has advanced to and is available in the clinic (Sipuleucel-T), the efficacy of such therapy remains limited. Here, we develop Immunostimulatory Spherical Nucleic Acid (IS-SNA) nanostructures comprised of CpG oligonucleotides as adjuvant and prostate cancer peptide antigens, and evaluate their antitumor efficacy in syngeneic mouse models of prostate cancer. IS-SNAs with the specific structural feature of presenting both antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…Previous work using model or syngeneic antigens has demonstrated that vaccine structure can influence the codelivery of adjuvant and antigen components, the intracellular trafficking and cross-presentation of antigens, and the kinetics of antigen processing signals. [44,48] However, herein, this work capitalizes on the translational promise of rational vaccinology by utilizing targets that allow for vaccine structure to be benchmarked and validated against clinical formulations. For these studies, we selected a SNA architecture that optimizes the efficacy of the three parameters: codelivery, trafficking, and kinetics.…”
Section: Synthesis Of Snas and Enhancement Of Antigen Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work using model or syngeneic antigens has demonstrated that vaccine structure can influence the codelivery of adjuvant and antigen components, the intracellular trafficking and cross-presentation of antigens, and the kinetics of antigen processing signals. [44,48] However, herein, this work capitalizes on the translational promise of rational vaccinology by utilizing targets that allow for vaccine structure to be benchmarked and validated against clinical formulations. For these studies, we selected a SNA architecture that optimizes the efficacy of the three parameters: codelivery, trafficking, and kinetics.…”
Section: Synthesis Of Snas and Enhancement Of Antigen Deliverymentioning
confidence: 99%
“…This was done through disulfide bond formation through a cysteine on the peptide's N-terminus and a 3ʹ-thiol functionalized to the CpG complement using previously published methods. [48] The peptides incorporated in the SNA, PSMA 711-719 or TARP 29-37-9V (Table S2, Supporting Information), come from two different PCa-upregulated proteins and were selected to illustrate the translatability of this platform across antigen selection. In particular, the TARP 29-37-9V mutated epitope-enhanced peptide was selected due to its improved immunogenicity and cytolytic capability.…”
Section: Synthesis Of Snas and Enhancement Of Antigen Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…A similar SNA technology, "sticky-flares", uses longer antisense sequences that allow the fluorophore to remain bound to the transcript, enabling the tracking of mRNA movement in the cell and changes in gene expression in real time [40]. Rapidly proliferating cancer cells with high telomerase activity can be identified using SNA oligos functionalized with telomerase primers, while immune cells can be conditioned to target cancer cells by loading SNAs with cancer cell lysates or antigens [41][42][43]. Antibodies can be conjugated to the DNA or absorbed onto the SNA for cell-specific targeting [44].…”
Section: Oligonucleotide Functional Additivesmentioning
confidence: 99%